2019
DOI: 10.1038/s41598-019-41399-4
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sargassum fusiforme improves memory and reduces amyloid plaque load in an Alzheimer’s disease mouse model

Abstract: Activation of liver X receptors (LXRs) by synthetic agonists was found to improve cognition in Alzheimer’s disease (AD) mice. However, these LXR agonists induce hypertriglyceridemia and hepatic steatosis, hampering their use in the clinic. We hypothesized that phytosterols as LXR agonists enhance cognition in AD without affecting plasma and hepatic triglycerides. Phytosterols previously reported to activate LXRs were tested in a luciferase-based LXR reporter assay. Using this assay, we found that phytosterols … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 81 publications
(85 reference statements)
4
62
0
Order By: Relevance
“…Studies on neuroprotective and antioxidant activities of Sargassum species have substantiated the role of various phytoconstituents. Presence of phenols, phytosterols, flavonoids, carotenoids, fucoxanthin, polysaccharides (fucoidan) and tannins in Sargassum (seaweeds) contribute to their promising antioxidant, antiinflammatory and neuroprotective properties [35][36][37]. The plant of our research interest, Sargassum wightii contains the same phytoconstituents.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on neuroprotective and antioxidant activities of Sargassum species have substantiated the role of various phytoconstituents. Presence of phenols, phytosterols, flavonoids, carotenoids, fucoxanthin, polysaccharides (fucoidan) and tannins in Sargassum (seaweeds) contribute to their promising antioxidant, antiinflammatory and neuroprotective properties [35][36][37]. The plant of our research interest, Sargassum wightii contains the same phytoconstituents.…”
Section: Discussionmentioning
confidence: 99%
“…For example, LXRα-selective antagonists or inverse agonists might be efficacious in the treatment of NAFLD without affecting reverse cholesterol transport 55 . On the other hand LXRβ-selective agonists are potentially useful to improve cognition in Alzheimer’s disease while avoiding stimulation of hepatic lipogenesis by LXRα, the predominant isoform in the liver 56 . GLUT5 expression is increased in the intestine and in skeletal muscle of T2D patients but also in certain cancers that are highly dependent on fructose uptake and metabolism, providing an alternative route for energy delivery during insulin resistance or to match increased energy demand caused by uncontrolled proliferation, respectively 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported neuroprotective role of astaxanthin and fucoxanthin [145, [282][283][284][285][286][287], Sargassum spp. [288][289][290][291][292][293][294][295], Saccorhiza polyschide [283], Codium tomentosum [296], Ulva spp [256,267,293,[297][298][299][300], Ecklonia maxima [256,[301][302][303], Gracilaria spp. (Figure 12) [296,[304][305][306][307][308][309][310][311], Gelidium pristoides [312,313], Halimeda incrassate [314,315], Bryothamniom triquetrum [316][317][318], Chondrus crispus ( Figure 13) [319,320], Hypnea valentiae (…”
Section: Neuroprotection In Stroke Alzheimer's and Parkinsonismmentioning
confidence: 99%